(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The effect of storage materials on the quality of tomato powder was studied. Fresh, firm and matured red tomatoes were washed, sorted and sliced to a uniform thickness of 5mm. The sliced tomatoes were pre-treated by dipping in 1% calcium chloride (CaCl2) and 0.2% potassium metabislphite (KMS) solution for 10 minutes at room temperature. 200g each of the sample was dried at temperatures of 600C until equilibrium moisture content was attained. The dried tomatoes were ground into powder and stored in Black polyethylene [BPE], White polyethylene [WPE], and Laminated Aluminium Foil [LAF] pouches for 6 weeks. The moisture content, crude protein, crude fibre, fat, total ash, and vitamin C of the tomato powder were determined using the method prescribed by AOAC. The carotene contents were determined by HPLC. The proximate analysis was repeated after 2 weeks, 4 weeks and 6weeks of storage. There was an increase in moisture content and ash content after 6 weeks of storage while a decrease in value of protein, fat and vitamin C content occurred after the storage period. All the parameters measured were best retained by the laminated aluminium foil (LAF) compared to black polyethylene (BPE) and white polyethylene (WPE) packaging material for the entire period of the study.